The relationship between social support and mental health in athletes: a systematic review and meta-analysis - Luo, J.; Du, R.; Wang, X.; Luo, L. (Frontiers in Psychology, 2025)
Introduction: Social support is widely recognized as a key determinant of athletes` mental health; however, inconsistencies remain regarding the strength and source-specific effects of this relationship. This meta-analysis systematically quantifies the association between social support and mental health outcomes in athletes and examines variations by support source.